Take your life back : how to stop letting the past and other people control you - Arterburn, Stephen, 1953-; Stoop, David (Tyndale Momentun, an imprint of Tyndale House Publishers, Inc., 2016)
Your past and current circumstances don't have to define you, and they don't have to determine the direction of your life. Arterburn and Stoop share the keys to moving from reactive attitudes and behaviors to healthy, God-honoring responses that will help you live the life you were meant to live.